1999
DOI: 10.1038/sj.ejcn.1600676
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption of young stunted and non-stunted children in rural Zambia

Abstract: Objective: The aim of this study was to assess the quality of diet of rural Zambian pre-school children, and to compare the dietary intake of stunted and non-stunted children. Design: Cross-sectional study, in which dietary intake was assessed with a 24-h recall method. Height and weight were measured according to standard procedures. Setting: Twelve villages in Samfya District, Zambia. Subjects: Children aged 6 ± 9 months (`infants') and 14 ± 20 months (`toddlers'), attending Mother-and-Child Health Clinics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 12 publications
7
38
1
2
Order By: Relevance
“…These findings parallel those for young breast-fed children living in other disadvantaged countries in South/South-East Asia (4,5,31,32) and sub-Saharan Africa (33)(34)(35) , where cereal-based complementary diets containing little micronutrient-dense cellular animal foods, dark-green vegetables or yellow-orange fruits predominate.…”
Section: Adequacy Of Energy and Nutrient Intakessupporting
confidence: 65%
“…These findings parallel those for young breast-fed children living in other disadvantaged countries in South/South-East Asia (4,5,31,32) and sub-Saharan Africa (33)(34)(35) , where cereal-based complementary diets containing little micronutrient-dense cellular animal foods, dark-green vegetables or yellow-orange fruits predominate.…”
Section: Adequacy Of Energy and Nutrient Intakessupporting
confidence: 65%
“…more animal protein was consumed in the intervention than the control group. Animal source foods, particularly flesh foods, are rich sources of iron, zinc, and sometimes calcium (eg small whole fish eaten with bones), but in low-income country settings, are often consumed in small amounts (Brown et al, 1982(Brown et al, , 2002Creed de Kanashiro et al, 1990;Hautvast et al, 1999). In a US study, fractional absorption of zinc tended to be higher in infants when beef was offered as the first complementary food in place of cereal to infants (Jalla et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the absorption of iron and zinc is modified substantially by dietary factors such as phytate and animal protein (FAO= WHO=IAEA, 1996;Wise, 1995). Few studies of complementary diets to date (Hautvast et al, 1999;Paul et al, 1998) have reported: (i) intakes of energy and multiple nutrients from complementary foods, independently of intakes from breastmilk; (ii) intake of dietary factors which modify absorption of iron and zinc and the consequent impact on their relative adequacy. Such information is necessary to assess the overall nutritional quality of the complementary diet and to develop suitable methods for its improvement.…”
Section: Introductionmentioning
confidence: 99%